Citrus Viroids in Northeastern Argentina: Diversity, Pathogenic Determinants and Host Interactions - Joris, Giovanna Lujan (2026)
Citrus is one of the most widely cultivated fruit crops worldwide, but its yield is threatened by pathogens, including viroids. Citrus species host several viroids, such as citrus exocortis viroid (CEVd) and specific variants of hop stunt viroid (HSVd), which cause exocortis and cachexia, respectively. Despite previous studies, knowledge regarding the distribution and genetic diversity of citrus viroids in Argentina remains scarce. In this study, Citrus sinensis samples were collected from three subregions of the northeastern Argentine citrus belt. Symptomatic field material was inoculated into Etrog citron (Citrus medica) for symptom evaluation, viroid identification and accumulation analysis. Molecular analyses revealed the presence of CEVd, HSVd and citrus dwarfing viroid (CDVd) occurring in single or mixed infections: 15% with CEVd alone, 50% with HSVd and CDVd and 35% with triple infections. Selected isolates from different subregions were inoculated into different hosts (tomato [Solanum lycopersicon], Etrog citron and cucumber [Cucumis sativus]) to investigate sequence determinants associated with pathogenicity. Local isolates showed distinct features: CEVd grouped into severe (A) and mild (B) categories, with group A accumulating to higher levels, carrying polymorphisms in the P and V domains and inducing tomato stunting. HSVd isolates corresponded to non-cachexia variants but induced growth delay in cucumber plants and CDVd clustered with CVd-IIIa and CVd-IIIb groups. In silico analysis revealed abundant P-domain-derived vd-siRNAs, with predicted host gene targets associated with symptom expression. This work represents the first comprehensive molecular characterisation of citrus viroids in northeastern Argentina, uncovering their diversity, pathogenic traits and potential host–pathogen interactions.